2010
DOI: 10.1002/mrm.22601
|View full text |Cite
|
Sign up to set email alerts
|

Determination of spin compartment in arterial spin labeling MRI

Abstract: A major difference between arterial-spin-labeling MRI and gold-standard radiotracer blood flow methods is that the compartment localization of the labeled spins in the arterialspin-labeling image is often ambiguous, which may affect the quantification of cerebral blood flow. In this study, we aim to probe whether the spins are located in the vascular system or tissue by using T2 of the arterial-spin-labeling signal as a marker. We combined two recently developed techniques, pseudo-continuous arterial spin labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
84
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(99 citation statements)
references
References 35 publications
11
84
1
Order By: Relevance
“…These results are in good agreement with prior studies using multi-TI PASL, which have reported transit times of 660-960 ms [6,8]. The LL-pCASL 90 mm data yielded transit times of 908 ± 170 ms (uncrushed) and 1463 ± 135 ms (crushed), also within the range of 600-1,600 ms reported by various other groups using multi-TI CASL [2,7,16,17]. Importantly, neither LL-ASL nor FEAST is capable of isolating transit to the tissue compartment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are in good agreement with prior studies using multi-TI PASL, which have reported transit times of 660-960 ms [6,8]. The LL-pCASL 90 mm data yielded transit times of 908 ± 170 ms (uncrushed) and 1463 ± 135 ms (crushed), also within the range of 600-1,600 ms reported by various other groups using multi-TI CASL [2,7,16,17]. Importantly, neither LL-ASL nor FEAST is capable of isolating transit to the tissue compartment.…”
Section: Discussionsupporting
confidence: 91%
“…Importantly, neither LL-ASL nor FEAST is capable of isolating transit to the tissue compartment. Other techniques such as detecting changes in T 2 of the spin label [16,18] or using stronger diffusion gradients to separate the capillary and tissue compartments [19] are necessary for accurate tissue transit time mapping.…”
Section: Discussionmentioning
confidence: 99%
“…They inferred that a postlabeling delay time of 2 seconds is sufficient to allow the spins to completely enter the tissue space for gray matter, and even longer inversion times are needed for white matter. 25 Therefore, we suggest that the most significant intratumoral signal intensity in our study depicts tumor circulation but not tumor perfusion and should be more precisely called "normalized vascular intratumoral signal LGA, diffuse astrocytoma; AA, anaplastic astrocytoma; GB, glioblastoma.…”
Section: Discussionmentioning
confidence: 83%
“…Recently, Liu et al 25 assessed the labeled spin localization at multiple postlabeling delay times by use of T2 of the arterial spin-labeling signal as a marker. Because of the T2 of arterial blood (approximately 152 ms) and the tissue T2 (approximately 90 ms), they proposed that especially at very low inversion times (below the average range of arterial transit time), the labeled spins are primarily located in arterial vessels.…”
Section: Discussionmentioning
confidence: 99%
“…This illustrates that the perfusion asymmetries in children with SCD as described before can at least partly be attributed to transit time effects. Recently, Liu et al (35) studied compartment localization of labeled spins in ASL and concluded that a postlabeling delay of 2000 msec is sufficient to allow the spins to completely enter the gray matter. Their data also suggested that all labeled spins exchange to tissue and that only very few remain in the vasculature to enter the vein.…”
Section: Discussionmentioning
confidence: 99%